TINJAUAN PENGATURAN PEMILIK MANFAAT (BENEFICIAL OWNERSHIP) TERHADAP KEPEMILIKAN PERSEROAN TERBATAS PERBANKAN DI INDONESIA (Studi PT. Bank Central Asia Tbk) - Achmad Dzulfadli Firdaus; Abdullah Sulaiman (JOURNAL of LEGAL RESEARCH, 2022)
Beneficial Owner is the concept of property ownership in the common law legal system which has 2 (two) types of property ownership, namely legal and beneficial. Indonesia as a country with a civil law legal system does not recognize beneficial ownership, and only recognizes legal ownership. Thus, the Regulation of Beneficiaries in Presidential Regulation Number 13 of 2018 concerning Application of the Recommendation of the Principle of Recognizing the Beneficial Owners of Corporations in the Context of Prevention and Eradication of the Crime of Money Laundering and Terrorism Financing Measures must be reviewed against the provisions of the ownership of the existing Banking Limited Liability Company. The purpose of this study is to explain the regulation of the Beneficiary on the provisions of the ownership of a Banking Limited Liability Company in Indonesia and specifically the ownership of PT Bank Central Asia Tbk.This study uses a type of qualitative research that is descriptive analysis using a normative research approach. This research was conducted using library research, where there are elements of a statutory approach using positive law in Indonesia and a conceptual approach. The regulations in this study are regarding the Beneficial Owner and Banking Limited Liability Company.The results of the study show that there is a discrepancy between the Beneficial Owners arrangement and Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 25 of 2007 concerning Investment and Financial Services Authority Regulation Number 39/POJK.03/2017 concerning Sole Proprietorship in Indonesian Banking . Furthermore, the criteria for Beneficial Owners in the ownership of PT Bank Central Asia Tbk are PT Investama Andalan which is owned by Robert Budi Hartono and Bambang Hartono who is the Controlling Shareholder of BCA.